2011
DOI: 10.1007/s12043-011-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum logic gates using coherent population trapping states

Abstract: A scheme is proposed for achieving a controlled phase gate using interaction between atomic spin dipoles. Further, the spin states are prepared in coherent population trap states (CPTs), which are robust against perturbations, laser fluctuations etc. We show that one-qubit and two-qubit operations can easily be obtained in this scheme. The scheme is also robust against decoherences due to spontaneous emissions as the CPT states used are dressed states formed out of Zeeman sublevels of ground states of the bare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The interaction leads to a dressed state that is a combination of all three ground states in such a way that it can be mapped to a state of the form |ψ〉 = sin(θ/2)|0〉 + exp(iϕ) cos(θ/2)|1〉. We have earlier shown that a discrete gate operation can be performed using this system (Vudayagiri, 2011). Here, we show that the same system can be used to perform continuous state preparation and, therefore, continuous operations as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction leads to a dressed state that is a combination of all three ground states in such a way that it can be mapped to a state of the form |ψ〉 = sin(θ/2)|0〉 + exp(iϕ) cos(θ/2)|1〉. We have earlier shown that a discrete gate operation can be performed using this system (Vudayagiri, 2011). Here, we show that the same system can be used to perform continuous state preparation and, therefore, continuous operations as well.…”
Section: Discussionmentioning
confidence: 99%
“…When both the π and σ lasers are simultaneously present in Figure 1, the system goes into a unique eigenstate involving all three states, which is of interest to the rest of the communication (Vudayagiri and Tewari, 2006;Vudayagiri, 2011). This unique state is the dressed state of the six-state Hamiltonian,…”
Section: Case Iii: Both π and σ Combinedmentioning
confidence: 99%
See 1 more Smart Citation